Egypt : Operational Framework for Integrated Rural Sanitation Service Delivery - World Bank (Washington, DC, 2012)
The Framework presented in this report links - for the first time in the Egyptian context - access to investment in rural sanitation services to quantifiable water quality (and health) improvements, in a given hydrologic basin. The Framework provides an integrated, institutional structure of relevant Government agencies and of serviced communities, which is built on integrated water resources management (IWRM) principles: treating water as a holistic resource, management at the lowest appropriate level, and inclusive stakeholder participation. The Framework's specific objectives include: 100% coverage of all houses within each project village with access to improved sanitation services; effective facilities for wastewater disposal; discontinued practice of discharging untreated domestic wastewaters into irrigation drains, canals, or storm drains; and, cost-effective measures for solid waste management. This Framework uses the hydrologic basin as the basic geographical unit to manage the quality of water in irrigation drains and canals, while envisaging a Strategic Management Unit at the national level, accountable to a Framework Advisory Board. The Management Unit will define water quality and other national goals for each hydrologic basin, in Branch Canal Water Board command areas, and within villages. Continued performance monitoring, and benchmarking at village and Branch Canal Water Board levels, is a key element in creating both the incentives, and public disclosure mechanisms for achieving, monitoring, and sustaining water quality and health goals. Government, donors, and beneficiaries will be the principal sources of financing. In view of other ongoing efforts in the water sector, the Bank could provide added value to the piloting, and the subsequent implementation of the Framework. This would be done by leveraging funds, and integrated capacity across the water resources, and water supply and sanitation sectors.